Phanerozoic trends in the global geographic disparity of marine biotas - Kießling, Wolfgang; et al. (Paleobiology, 2009)
Previous analyses of the history of Phanerozoic marine biodiversity suggested that the post-Paleozoic increase observed at the family level and below was caused, in part, by an increase in global provinciality associated with the breakup of Pangea. Efforts to characterize the Phanerozoic history of provinciality, however, have been compromised by interval-to-interval variations in the methods and standards used by researchers to calibrate the number of provinces. With the development of comprehensive, occurrence-based data repositories such as the Paleobiology Database (PaleoDB), it is now possible to analyze directly the degree of global compositional disparity as a function of geographic distance (geo-disparity) and changes thereof throughout the history of marine animal life. Here, we present a protocol for assessing the Phanerozoic history of geo-disparity, and we apply it to stratigraphic bins arrayed throughout the Phanerozoic for which data were accessed from the PaleoDB. Our analyses provide no indication of a secular Phanerozoic increase in geo-disparity. Furthermore, fundamental characteristics of geo-disparity may have changed from era to era in concert with changes to marine venues, although these patterns will require further scrutiny in future investigations. © 2009 The Paleontological Society. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.LP.phaner